The Kinship of Pesisir Barus, Pesisir Singkuang and Batak Toba Languages - Suci Audina Sihotang; Dwi Widayati; Dardanila Dardanila (Budapest International Research and Critics University, 2022)
This research belongs to the type of comparative historical linguistic research with the aim of looking at the kinship between the Pesisi Barus Language, Pesisir Singkuang Language and Toba Batak Language. This study uses a quantitative method with lexicostatistical and glotochronological data analysis. The data collection method used in the form of interviews and listen to the tapping technique and recording technique. The data used in this research is basic vocabulary which contains 300 basic vocabulary. The data sources of this research are in the form of oral and written forms, sourced directly from the results of speaker interviews. The results of this study include (1) the kinship between the Pesisir Barus Language and the Pesisir Singkuang Language there are 197 identical pairs, 61 phonemic correspondence pairs, 61 phonetically similar pairs, and 43 pairs with one distinct phoneme. (2) The kinship between the Pesisir Barus Language and Toba Batak Language is 27 identical pairs, 60 phonemic correspondence pairs, 44 phonetically similar pairs and 35 pairs with one different phoneme. (3) The kinship between Pesisir Singkuang Language and Toba Batak Language contained 29 identical pairs, 61 phonemic correspondence pairs, 43 phonetically similar pairs, and 28 pairs with one different phoneme.